(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Nowadays people are more willing to spend money on travel than ever before they are looking forward to opening borders after the global pandemic. New possibilities make traveling easier and travelers can choose options quicker for immediate travel. Travelers do not have to check special hotels in a chosen destination and compare prices to find the most suitable or cheapest option. Web-sites, as well as mobile applications in tourism, can do that for them, making traveling much simpler, easier and more comfortable. Tourism is fast-growing industry becoming more popular day by day and the main aim of the research was to study the role of digital technologies in tourism, especially during COVID-19.